Kajian Keragaan Beberapa Varietas Unggul Baru Padi Gogo di Lahan Sub-Optimal Gunungkidul, Yogyakarta - Bambang Sutaryo; S. Widodo (Seminar Nasional Lahan Suboptimal, 2018)
Sutaryo et al, 2019. Study on Performance for Some New Upland Rice Superior Varieties in Sub-Optimal Area in Gunungkidul, Yogyakarta. pp. 449-455.This research aimed to study on performance for some new upland rice superior varieties in sub-optimal area in Gunungkidul, Yogyakarta.  Study on performance for some new upland rice superior varieties in sub-optmal area in Gunungkidul, Yogyakarta  using Inpago 5, Inpago 8, and Inpago 10 was conducted at Kumpul Makaryo Farmer Group, Nglanggeran, Patuk, Gunungkidul, Yogyakarta from February 2017- June 2017. Seedling of  15 days with one seedling per hill was planted in tajarwo 4:1, spacing of 25 x 12,5 x 50 cm, with  256.000 plant population. Plot size per variety was  2000 m2. Those varieties were used as treatment. Ciherang as a  populair varieties planted using the same population by farmers were used as checks. Data were analyzed using t test. Inpago 5 gave the highest yield (7.3 t/ha) compared with check varieties and the other varieties tested, with yield ranging from 5.9 for Ciherang to 7.0 t/ha for Inpago 8. The highest yield on Inpago 5 was contributed by the highest of the main components, namely the number of filled grains, total grain number, and the panicle number. All varieties showed early to moderate maturity ranging from 107 days for Inpago 5 to 116 days for Ciherang. Inpago 5, Inpago 8 and Inpago 10  should be developed on a broad scale.